Ravana's kingdom: the Ramayana and Sri Lankan history from below - Henry, Justin W. (Oxford University Press, 2023)
"Ravana, the demon-king antagonist from the Ramayana, the ancient Hindu epic poem, has become an unlikely cultural hero among Sinhala Buddhists over the past decade. In Ravana's Kingdom, Justin W. Henry delves into the historical literary reception of the epic in Sri Lanka, charting the adaptions of its themes and characters from the 14th century onwards, as many Sri Lankan Hindus and Buddhists developed a sympathetic impression of Ravana's character, and through the contemporary Ravana revival, which has resulted in the development of an alternative mythological history, depicting Ravana as king of the Sri Lanka's indigenous inhabitants, a formative figure of civilizational antiquity, and the direct ancestor of the Sinhala Buddhist people. Henry offers a careful study of the literary history of the Ramayana in Sri Lanka, employing numerous sources and archives that have until now received little to no scholarly attention, as well as the 21st century revision of a narrative of the Sri Lankan people-a narrative incubated by the general public online, facilitated by social media and by the speed of travel of information in the digital age. Ravana's Kingdom offers a glimpse into a centuries-old, living Ramayana tradition among Hindus and Buddhists in Sri Lanka-a case study of the myth-making process in the digital age"